Transforming primary human hepatocytes into hepatocellular carcinoma with genetically defined factors. (19th April 2022) - Jiang, Zhiwu; Cheng, Lin; Wu, Zhiping; Zhou, Linfu; Wang, Haitao; Hong, Qilan; Wu, Qiting; Long, Youguo; Huang, Yunlin; Xu, Gaoqi; Yao, Yao; Tang, Zhaoyang; et al.
Abstract: Our understanding of human hepatocellular carcinoma (HCC) development and progression has been hampered by the lack of in vivo models. We performed a genetic screen of 10 oncogenes and genetic mutations in Fah ‐ablated immunodeficient mice in which primary human hepatocytes (PHHs) are used to reconstitute a functional human liver. We identified that MYC, TP53 R249S, and KRAS G12D are highly expressed in induced HCC (iHCC) samples. The overexpression of MYC and TP53 R249S transform PHHs into iHCC in situ, though the addition of KRAS G12D significantly increases the tumorigenic efficiency. iHCC, which recapitulate the histological architecture and gene expression characteristics of clinical HCC samples, reconstituted HCC after serial transplantations. Transcriptomic analysis of iHCC and PHHs showed that MUC1 and FAP are expressed in iHCC but not in normal livers. Chimeric antigen receptor (CAR) T cells against these two surface markers efficiently lyse iHCC cells. The properties of iHCC model provide a biological basis for several clinical hallmarks of HCC, and iHCC may serve as a model to study HCC initiation and to identify diagnostic biomarkers and targets for cellular immunotherapy. Synopsis: The understanding of hepatocellular carcinoma development and progression is hampered by the lack of in vivo models. This study presents an in situ mouse model of human induced HCC that allows studying HCC initiation and the identification of biomarkers. MYC, TP53 R249S, and KRAS G12D are highly expressed in induced HCC (iHCC) samples. Overexpression of these factors transforms primary human hepatocytes into iHCC in Fah‐ablated immunodeficient mice. iHCC recapitulates the transcriptional profiles and hallmarks of human HCC. The iHCC mouse model permits the identification of diagnostic and therapeutic targets for HCC. Abstract : The understanding of hepatocellular carcinoma development and progression is hampered by the lack of in vivo models. This study presents an in situ mouse model of human induced HCC that allows studying HCC initiation and the identification of biomarkers.